2014
DOI: 10.2478/intag-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Kinetics of Atrazine and Inorganic Chemicals in Tilled and Orchard Soils

Abstract: A b s t r a c t. The aim of this study was to verify first-order kinetic reaction rate model performance in predicting of leaching of atrazine and inorganic compounds (K -and PO 4 -3 ) from tilled and orchard silty loam soils. This model provided an excellent fit to the experimental concentration changes of the compounds vs. time data during leaching. Calculated values of the first-order reaction rate constants for the changes of all chemicals were from 3.8 to 19.0 times higher in orchard than in tilled soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…K is the first-order rate constant in units of L/time, and the reaction rate unit is presented as concentration/time. The units can vary with other order reactions (Szajdak et al, 2014) Table 2 shows the statistical parameters of the first-order kinetics model with a good fit for the measured concentration change over time (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…K is the first-order rate constant in units of L/time, and the reaction rate unit is presented as concentration/time. The units can vary with other order reactions (Szajdak et al, 2014) Table 2 shows the statistical parameters of the first-order kinetics model with a good fit for the measured concentration change over time (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
“…This difference could be a result of the higher organic matter and the specific interaction between nonionic-2 and organic matter. Szajdak et al (2014) showed that higher K values are associated with higher organic matter. The effect of nonionic-1 on K values could be attributed to the fumigant staying longer in solution and not adsorbing on soil particles, thereby possibly increasing fumigant residence time in soil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first-order interaction model is used to study the leaching of chemical compounds and nutrients from the soil, which helps to predict the actual concentration of these compounds and the interactions between these compounds and the soil as a result of the management practices 71 . Physicochemical properties of the soils such as texture, bulk density, organic carbon, and pH have a great impact on the rate constants of a first-order reaction.…”
Section: Discussionmentioning
confidence: 99%